The Effect of Working Capital Turnover and Leverage on Profitability, with Company Size as a Mediating Variable - Durotun Nafisa; Wiwit Apit Sulistyowati (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of Working Capital Turnover and Leverage on Profitability with Firm Size as a mediating variable in manufacturing companies within the non-cyclical consumer goods subsector listed on the Indonesia Stock Exchange (IDX). The study population consisted of 132 companies, and the data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings reveal that Working Capital Turnover has a significant negative effect on Profitability but does not significantly affect Firm Size. Leverage has a significant positive effect on Firm Size but does not have a significant direct effect on Profitability. In addition, Firm Size has a significant negative effect on Profitability, indicating that an increase in company assets does not necessarily result in a proportional increase in profit generation. The mediation analysis shows that Firm Size does not mediate the relationship between Working Capital Turnover and Profitability, whereas it significantly and negatively mediates the relationship between Leverage and Profitability. These results suggest that leverage can encourage firm growth through increased assets; however, such growth may reduce profitability. Overall, the study confirms that the relationship between financial structure and profitability is not always direct and can be influenced by indirect mechanisms through Firm Size. Therefore, companies should focus on effective working capital management and optimal leverage utilization to ensure that business growth is accompanied by improved profitability. Furthermore, this study contributes to the corporate finance literature by highlighting the importance of mediating variables in explaining the relationship between financial factors and firm performance.